Experimental study of heat transfer from the gas-vapor mixture to the surface in rectangular channel with the water vapor condensation; Journal of Physics: Conference Series; Vol. 754 : Thermophysics and Physical Hydrodynamics - Bespalov V. V. Viktor Vladimirovich (2016, 2016)
Title screen